Evolution of the HCV viral population from a patient with S282T detected at relapse after sofosbuvir monotherapy. Issue 11 (18th March 2015) - Hedskog, C.; Dvory‐Sobol, H.; Gontcharova, V.; Martin, R.; Ouyang, W.; Han, B.; Gane, E. J.; Brainard, D.; Hyland, R. H.; Miller, M. D.; Mo, H.; Svarovskaia, E.
Summary Clinical phase II/III studies of the nucleotide analogue HCV NS5B inhibitor sofosbuvir (SOF) have demonstrated high efficacy in HCV‐infected patients in combination therapy. To date, resistance to SOF (S282T in NS5B) has rarely been detected in patients. In this study, we investigated the evolution of S282T viral variants detected in one HCV genotype 2b‐infected patient who relapsed following 12 weeks of SOF monotherapy. Deep sequencing of the NS5B gene was performed on longitudinal plasma samples at baseline, days 2 and 3 on SOF, and longitudinal samples post‐SOF treatment through week 48. Intrapatient HCV evolution was analysed by maximum‐likelihood phylogenetic analysis. Deep sequencing analysis revealed a low level pre‐existence of S282T at 0.05% of viral sequences (4/7755 reads) at baseline and 0.03% (6/23 415 reads) at day 2 on SOF. Viral relapse was detected at week 4 post‐treatment where 99.8% of the viral population harboured S282T. Follow‐up analysis determined that S282T levels diminished post‐treatment reaching undetectable levels 24–48 weeks post‐SOF. Phylogenetic analysis together with the persistence of unique post‐treatment mutations in all post‐SOF samples suggested that growth of wild type resulted from reversion of the S282T mutant to a wild type and not outgrowth of the baseline wild‐type population. Our data suggest that a very low level of pre‐existing S282T at baseline in this patient was enriched and transiently detected following SOF monotherapy. Despite relapse with drug resistance to SOF, this patient was successfully retreated with SOF plus ribavirin for 12 weeks and is now cured from HCV infection.